How do you find the particular solution to #ysqrt(1-x^2)y'-x(1+y^2)=0# that satisfies y(0)=sqrt3?

Answer 1

Use the separation of variables method, integrate both sides, and then use the specified point to evaluate the constant.

Given: #ysqrt(1 - x^2)y' - x(1 + y^2) = 0; y(0) = sqrt(3)#
Use the notation #dy/dx# for y':
#ysqrt(1 - x^2)dy/dx - x(1 + y^2) = 0#

Move the second term to the right side:

#ysqrt(1 - x^2)dy/dx = x(1 + y^2)#
Multiply both sides of the equation by #dx/(sqrt(1 - x^2)(1 + y^2))#
#y/(1 + y^2)dy = x/sqrt(1 - x^2)dx#

Integrate both sides:

#inty/(1 + y^2)dy = intx/sqrt(1 - x^2)dx#
#(1/2)ln(1 + y^2) = -sqrt(1 - x^2) + C#

Multiply both sides by 2:

#ln(1 + y^2) = -2sqrt(1 - x^2) + C#

Use the exponential function:

#1 + y^2 = e^(-2sqrt(1 - x^2) + C)#

Adding a constant in the exponent is the same as multiplying by a constant:

#1 + y^2 = Ce^(-2sqrt(1 - x^2))#

Subtract 1 from both sides:

#y^2 = Ce^(-2sqrt(1 - x^2)) - 1#

Square root both sides:

#y = +-sqrt(Ce^(-2sqrt(1 - x^2)) - 1)" [1]"#
Use the point to solve for C, substitute 0 for x and #sqrt(3)# for y:
#sqrt(3) = +-sqrt(Ce^(-2sqrt(1 - 0^2)) - 1)#
The above equation can only be true, if we can drop the #+-# and make it only positive:
#sqrt(3) = sqrt(Ce^(-2sqrt(1 - 0^2)) - 1)#

Square both sides and solve for C:

#3 = Ce^-2 - 1#
#4 = Ce^-2#
#C = 4e^2#
Substitute #4e^2# for C and remove the #+-# in equation [1]:
#y = sqrt((4e^2)e^(-2sqrt(1 - x^2)) - 1)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the particular solution to the differential equation ( y\sqrt{1-x^2}y' - x(1+y^2) = 0 ) that satisfies ( y(0) = \sqrt{3} ), follow these steps:

  1. Rewrite the differential equation in standard form.
  2. Separate variables and integrate both sides.
  3. Solve for ( y ) to find the particular solution.
  4. Use the initial condition ( y(0) = \sqrt{3} ) to determine the constant of integration.

Step 1: Rewrite the differential equation: [ y\sqrt{1-x^2} \frac{dy}{dx} = x(1+y^2) ]

Step 2: Separate variables and integrate: [ \int \frac{y}{1+y^2} , dy = \int \frac{x}{\sqrt{1-x^2}} , dx ]

Step 3: Solve for ( y ): [ \frac{1}{2} \ln(1+y^2) = -\frac{1}{2} \arcsin(x^2) + C ]

[ \ln(1+y^2) = -\arcsin(x^2) + C_1 ]

[ 1 + y^2 = e^{-\arcsin(x^2) + C_1} ]

[ y^2 = e^{-\arcsin(x^2) + C_1} - 1 ]

[ y = \pm \sqrt{e^{-\arcsin(x^2) + C_1} - 1} ]

Step 4: Apply the initial condition ( y(0) = \sqrt{3} ) to find ( C_1 ): [ \sqrt{3} = \sqrt{e^{-\arcsin(0)} - 1} ] [ \sqrt{3} = \sqrt{e^0 - 1} ] [ \sqrt{3} = \sqrt{1} ] [ C_1 = 0 ]

Therefore, the particular solution satisfying ( y(0) = \sqrt{3} ) is: [ y = \sqrt{e^{-\arcsin(x^2)}} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7